Lean as a new innovative method in education system (Eurasian Journal of Philology Science and Education, 2019)
Nowadays there are many investigations in education system, which discover and provide newmethods and approaches, which help to tech and learn in effective way. In this paper we studied a newinnovative method as Lean. We examine the history of this method, its effectiveness and role in education system, and tried to distinguish advantages and disadvantages of this method.